Incentives to invest in electronic coordination: Under- or overinvestment in equilibrium? - Martin Bandulet; Karl Morasch (Universität Augsburg, Institut für Volkswirtschaftslehre, 2001)
Do firms have proper incentives to invest in electronic coordination? We discuss this question in an oligopoly model with a local firm and a distant competitor that may reduce transport costs by investing in electronic coordination. In a two-stage game with investment in the first stage and price or quantity competition with differentiated products in the second stage we compare profit maximizing investment with (constrained) welfare maximization by a social planer. Depending on market demand, firm conduct and investment costs either over- or underinvestment may result: The firm will overinvest if the negative impact on its competitor exceeds the gain in consumer surplus. This is shown to be especially likely under quantity competition with (almost) homogenous products.
urn:nbn:de:bvb:384-opus4-276637
Keywords: D43; D61; L13; 330; Electronic Markets; Strategic Investments; Transport Costs; Product Differentiation